RF MEMS reference oscillators platform for wireless communications - Kourani, Ali (AUC Knowledge Fountain, 2015)
A complete platform for RF MEMS reference oscillator is built to replace bulky quartz from mobile devices, thus reducing size and cost. The design targets LTE transceivers. A low phase noise 76.8 MHz reference oscillator is designed using material temperature compensated AlN-on-silicon resonator. The thesis proposes a system combining piezoelectric resonator with low loading CMOS cross coupled series resonance oscillator to reach state-of-the-art LTE phase noise specifications. The designed resonator is a two port fundamental width extensional mode resonator. The resonator characterized by high unloaded quality factor in vacuum is designed with low temperature coefficient of frequency (TCF) using as compensation material which enhances the TCF from - 3000 ppm to 105 ppm across temperature ranges of -40˚C to 85˚C. By using a series resonant CMOS oscillator, phase noise of -123 dBc/Hz at 1 kHz, and -162 dBc/Hz at 1MHz offset is achieved. The oscillator’s integrated RMS jitter is 106 fs (10 kHz–20 MHz), consuming 850 μA, with startup time is 250μs, achieving a Figure-of-merit (FOM) of 216 dB. Electronic frequency compensation is presented to further enhance the frequency stability of the oscillator. Initial frequency offset of 8000 ppm and temperature drift errors are combined and further addressed electronically. A simple digital compensation circuitry generates a compensation word as an input to 21 bit MASH 1 -1-1 sigma delta modulator incorporated in RF LTE fractional N-PLL for frequency compensation. Temperature is sensed using low power BJT band-gap front end circuitry with 12 bit temperature to digital converter characterized by a resolution of 0.075˚C. The smart temperature sensor consumes only 4.6 μA. 700 MHz band LTE signal proved to have the stringent phase noise and frequency resolution specifications among all LTE bands. For this band, the achieved jitter value is 1.29 ps and the output frequency stability is 0.5 ppm over temperature ranges from -40˚C to 85˚C. The system is built on 32nm CMOS technology using 1.8V IO devices